First Report of 16SrI-B Subgroup Related Phytoplasma Associated with Yellows Symptoms of Rubus cochinchinensis in China - Lin, ZhaoWei (Plant disease, 2023)
Rubus cochinchinensis, an important traditional Chinese medicine in China is used to treat rheumatic arthralgia, bruises and lumbocrural pain (He et al.2005). In January 2022, yellow leaves of R. cochinchinensis were found in Tunchang City, Hainan Province, a tropical island in China. Chlorosis spread along the direction of vascular tissue while the leaf veins remain green (Fig. 1). In addition, the leaves were slightly shrunken and the growth vigor is poor (Fig. 1). By survey, we found the incidence of this disease was about 30%. Three etiolated samples and three healthy samples (0.1g each) were used to extract total DNA (TIANGEN plant genomic DNA extraction kit). Using nested PCR method, phytoplasma universal primers P1 / P7 (Schneider et al., 1995) and R16F2n / R16R2 (Lee et al. 1993) were used to amplified phytoplasma 16S rDNA gene. Primers rp F1 / R1 (Lee et al. 1998) and rp F2 / R2 (Martini et al. 2007) were used to amplified rp gene. 16S rDNA gene and rp gene fragments were amplified from three leaf etiolated samples, but not from healthy samples. The amplified fragments were cloned and sequenced, and the sequences were assembled by DNASTAR11. By sequence alignment, we found the obtained 16S rDNA and rp gene sequences of three leaf etiolated samples were same. The length of 16S rDNA fragment was 1237 bp (accession number: ON944105) and the length of rp gene fragment was 1212 bp (accession number: ON960069). The phytoplasma strain was named as 'R. cochinchinensis' yellows leaf phytoplasma (RcT), RcT-HN1 strain. The 16S rDNA gene sequence of RcT-HN1is 99.8% consistent with 16SrI-B subgroup members such as the 'Brassica napus' dwarf phytoplasma strain WH3 (MG599470.1), Chinaberry yellows phytoplasma strain LJM-1(KX683297.1) and Arecanut yellow leaf disease phytoplasma strain B165 (FJ694685.1). The rp gene sequence of RcT-HN1 is 100% consistent with rpI-B subgroup members such as the 'Salix tetradenia' witches'-broom phytoplasma strain YM-1 (KC117314.1) and Chinaberry witches'-broom phytoplasma strain Hainan (EU348781.1). The phylogenetic tree analysis, based on concatenated 16S rDNA-rp gene sequence of same group phytoplasma by MEGA 7.0 employing neighbor-joining (NJ) method with 1000 bootstrap value, were performed (Kumar et al., 2016). The results showed that RcT-HN1 phytoplasma strain formed a subclade in aster yellows group B subgroup (Fig. 2). The virtual RFLP analysis based on the 16S rRNA gene fragment of RcT-HN1 phytoplasma strain was performed by the interactive online phytoplasma classification tool iPhyClassifier (Zhao et al., 2009). The results showed that the phytoplasma strain was same as the reference pattern of the onion yellows phytoplasma of 16SrI-B (GenBank accession: AP006628), and the similarity coefficient was 1.00. This is the first report that 16SrI-B subgroup related phytoplasma infected R. cochinchinensis and caused yellows symptoms in China. The discovery of the disease is helpful to the study of the spread of phytoplasma-related diseases and protect R. cochinchinensis resources